2022
DOI: 10.1186/s12935-022-02527-9
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated macrophage derived IL-6 enriches cancer stem cell population and promotes breast tumor progression via Stat-3 pathway

Abstract: Background Cancer stem cells (CSCs) play crucial role in tumor progression, drug resistance and relapse in various cancers. CSC niche is comprised of various stromal cell types including Tumor-associated macrophages (TAMs). Extrinsic ques derived from these cells help in maintenance of CSC phenotype. TAMs have versatile roles in tumor progression however their function in enrichment of CSC is poorly explored. Methods Mouse macrophages (RAW264.7) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 48 publications
1
63
0
Order By: Relevance
“…Taken together, this data suggests that interactions between tissue damaged from RT and M2 and M1 macrophages causes secretion of IL-6 that in turn recruits 4T1 cells ( Figure 4C ). Myeloid-derived IL-6 has been reported in 4T1 progression and metastasis 33,34 . However, this is the first report of IL-6 driving 4T1 invasiveness post-RT in the context of recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, this data suggests that interactions between tissue damaged from RT and M2 and M1 macrophages causes secretion of IL-6 that in turn recruits 4T1 cells ( Figure 4C ). Myeloid-derived IL-6 has been reported in 4T1 progression and metastasis 33,34 . However, this is the first report of IL-6 driving 4T1 invasiveness post-RT in the context of recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…These results further differentiate, from a molecular point of view, the two GBM subgroups, assigning a specific IL6-NANOG signature to the KDM5C High . Since IL6 overexpression is induced by hypoxia [ 65 ], and as IL6 may strongly induce NANOG expression and promote proliferation and stemness in other tumors [ 66 , 67 , 68 ], the co-expression of IL6-NANOG likely represents a hypoxia-induced module, which appears as a distinctive feature of the KDM5C High GBM phenotype. Nevertheless, our results further emphasize TREM2 as a GBM biomarker, as recently reported [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, high expression of IL6 was identified in HSPB1-overexpressing group, and the inhibited expression of IL6 caused by HSPB1 knockdown could be rescued by IKβ-α knockdown. IL6 could be secreted from various cells in cancer tissues, including myeloid cells, cancer-associated fibroblasts, and cancer cells (4547). Our results revealed that HSPB1 overexpression promoted the secretion of IL6, whereas HSPB1 knockdown led to decreased IL6 secretion in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%